Blockchain Adoption for Improving Business Transparency and Accountability in Indonesia - Karamoy, Mianda; Mamesah, Ryan; Sarani, saranani@gmail.com (Inspirasi & Strategi (INSPIRAT): Jurnal Kebijakan Publik & Bisnis, 2026)
Business transparency remains a critical issue in Indonesia, where challenges such as fraud, data manipulation, and limited accountability continue to undermine trust in business practices. The increasing complexity of economic activities highlights the need for more reliable and secure systems to ensure data integrity and openness. This study aims to analyze the role of blockchain technology in improving business transparency in Indonesia. The research employs a qualitative descriptive approach, supported by a literature review and case study analysis of blockchain applications in sectors such as finance, supply chain, and public services. The findings indicate that blockchain significantly enhances transparency through its key features, including immutable records, decentralized data management, and real-time transaction tracking. These characteristics contribute to increased trust among stakeholders, reduced opportunities for fraud, and improved traceability of business processes. Furthermore, blockchain demonstrates potential in strengthening accountability and operational efficiency compared to traditional centralized systems. However, challenges such as regulatory uncertainty, limited infrastructure, and high implementation costs remain barriers to widespread adoption. In conclusion, blockchain technology is an effective and promising solution for improving business transparency in Indonesia, particularly when supported by appropriate policies, infrastructure development, and increased digital literacy.